2014
DOI: 10.1002/adsc.201300786
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants for the Non‐Canonical Substrate Specificity of the ω‐Transaminase from Paracoccus denitrificans

Abstract: Substrate binding pockets of ω‐transaminase (ω‐TA) consist of a large (L) pocket capable of dual recognition of hydrophobic and carboxyl substituents, and a small (S) pocket displaying a strict steric constraint that permits entry of a substituent no larger than an ethyl group. Despite the unique catalytic utility of ω‐TA enabling asymmetric reductive amination of carbonyl compounds, the severe size exclusion occurring in the S pocket has limited synthetic applications of ω‐TA to access structurally diverse ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…Besides the L57A variant, the V154A variant was the only alanine substitution variant that allowed an improvement in activity for 2-oxopentanoic acid (i.e., a 3-fold increase). This result is in line with our previous observation that an alanine substitution at the same position of the -TA from P. denitrificans achieved excavation of the small pocket (29). Site-directed mutagenesis of L57.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Besides the L57A variant, the V154A variant was the only alanine substitution variant that allowed an improvement in activity for 2-oxopentanoic acid (i.e., a 3-fold increase). This result is in line with our previous observation that an alanine substitution at the same position of the -TA from P. denitrificans achieved excavation of the small pocket (29). Site-directed mutagenesis of L57.…”
Section: Resultssupporting
confidence: 81%
“…This leads all known -TAs to accept a limited range of ␣-keto acids, such as glyoxylic acid, pyruvic acid, and 2-oxobutyric acid. The only exception to the canonical substrate specificity to date is an (S)-selective -TA from Paracoccus denitrificans that can accommodate substituents whose bulk is up to that of an n-butyl substituent of ␣-keto acid in the small pocket (29). We demonstrated that a single point mutation in the small pocket (i.e., V153A) endowed the -TA with substantial activity toward even 2-oxooctanoic acid carrying an n-hexyl side chain (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 The enzyme topology for this class of enzymes has been well elucidated and it can be easily described by two pockets surrounding the cofactor pyridoxal phosphate (PLP). 16,17 The large one accepts bulky groups such as aromatic rings, while the second, smaller one, accommodates short hydrophobic groups.…”
Section: Resultsmentioning
confidence: 99%
“…9 On the other hand, unfavourable steric interactions between the enzyme and the substrate may hamper the reactivity and can only be gauged after investigation of the enzyme-substrate binding mode. 10 Beside stereoelectronic effects involved in the enzymatic interactions, water solubility of hydrophobic substrates may also strongly influence the reactivity. Therefore, in attempt to characterise the electronic behaviour of the amino transferase from Halomonas elongata (HEWT), 11 we investigated the role of different substituents on aromatic ketones, aldehydes, and the corresponding (S)-amines.…”
Section: Introductionmentioning
confidence: 99%